Emergence of floating offshore wind energy: technology and industry - Bento, Nuno (2020)
ABSTRACT: The paper investigates the construction of strategies aiming to up-scale low-carbon innovations from pilot to full commercial scale. This requires a systemic understanding of the evolution of the technology along with the organizations and infrastructures supporting its development. Technological innovation systems concepts operationalize system building processes, including the establishment of constituent elements and the performance of key innovation activities. The study surveys the national roadmaps published between 2009 and 2014 for offshore wind energy in deepwaters (more than 50 m deep) which inform on how actors expect the system to grow, including the innovation activities crucial to achieve it. The roadmaps point to the role of guidance and legitimacy as triggers of changes in other innovation processes (knowledge creation, experimentation and so on) needed for take-off. The analysis reveals that the growth plans conveyed in the roadmaps are overly optimistic when compared with the time taken to develop offshore wind energy in fixed structures for shallow waters. Several countries have adopted supporting policies following the publication of the roadmaps, but weaknesses in crucial innovation processes (e.g. specialized skills) and external factors (e.g. crisis, regulatory approval) resulted in a delay of the first large investments. Policy should be based on realistic expectations and adequate to the phase of innovation, such as the promotion of technology-specific institutions (standards, codes, regulations and so on) in technology up-scaling. New directions for research are also provided.